How Facebook Adoption Impacts SMEs Performance - Richard, Mugarura; Osunsan, Olutayo; Onyait, Samuel; Augustine, Wandiba (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
The rise in social media usage has revolutionized information dynamics, transforming traditional communication into a multidirectional, interactive process. This study explores the impact of Facebook adoption on Small and Medium-sized Enterprises (SMEs) performance, addressing a notable gap in the Ugandan context. A quantitative survey involving 120 SMEs employed a comprehensive questionnaire validated for content and reliability. Existing literature suggests that Facebook positively influences SME performance, more so in areas like cost-effective marketing and customer engagement. Results highlight a moderate to high levels of Facebook adoption among SMEs. Correlation analysis reveals positive associations between Facebook adoption and SME performance. Regression analysis further signifies Facebook's significant impact ( =0.142, P<0.0003), particularly through customer engagement (B=0.263, p<0.029). The study points out the unique relationship between Facebook adoption and SME performance and thus recommend businesses to strategically engage with customers on this platform. While the model explains a part of SME performance, areas for future research to explore additional influencing factors are recommended.